2022
DOI: 10.1038/s41565-022-01144-x
|View full text |Cite
|
Sign up to set email alerts
|

Current-driven dynamics and ratchet effect of skyrmion bubbles in a ferrimagnetic insulator

Abstract: Funding acknowledgement:200465 -Interconversion of charge, spin and heat currents in spintronic devices (SNF) 178825 -Dynamical processes in systems with strong electronic correlations (SNF) 694955 -In-situ second harmonic generation for emergent electronics in transition-metal oxides (EC) SEED-20 19-2 -Electrical manipulation and imaging of domains in antiferromagnets (ETHZ)This page was generated automatically upon download from the ETH Zurich Research Collection. For more information, please consult the Ter… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 58 publications
1
37
0
Order By: Relevance
“…4c and 4d. Thus, an additional state is visible and this irreversible behavior manifests a similar SOT ratchet effect in a single layer RE-TM ferrimagnetic alloy as in AFM/FM systems 35,37,41 . SOT switching curve with varying external symmetry breaking field (B x ) and initialization with B set,z of +100 mT and -100 mT respectively.…”
Section: Resultsmentioning
confidence: 75%
“…4c and 4d. Thus, an additional state is visible and this irreversible behavior manifests a similar SOT ratchet effect in a single layer RE-TM ferrimagnetic alloy as in AFM/FM systems 35,37,41 . SOT switching curve with varying external symmetry breaking field (B x ) and initialization with B set,z of +100 mT and -100 mT respectively.…”
Section: Resultsmentioning
confidence: 75%
“…By contrast, the SH wave can e ciently move skyrmions as a result of the strong magnetoelastic coupling induced by the in-plane strain gradients. The observed directional motion shows a longitudinal component along the wave propagation direction, and a transverse component with the sign depending on the topological charges, in analogy to the skyrmion Hall effect 12,43 . These experimental observations are further con rmed by our micromagnetic simulations.…”
mentioning
confidence: 76%
“…Spin ratchet effects, which can open novel ways for efficient generation and control of spin fluxes [28], attracted growing attention. Since the first work, several different origins of spin ratchet currents have been suggested and discussed [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45], for review see [46]. For example, it has been shown that a stationary spin current can be generated by applying an ac driving current to a symmetric or asymmetric periodic structure with Rashba spin-orbit coupling.…”
Section: Introductionmentioning
confidence: 99%